A lithium iron phosphate positive electrode slurry, a positive electrode sheet, a preparation method thereof, and a battery
By modifying conductive agents to prepare lithium iron phosphate cathode slurry, the defects of lithium iron phosphate materials in terms of cycle performance and other properties are solved, the conductivity and structural stability of lithium-ion batteries are improved, battery life is extended, and application scenarios are broadened.
Patent Information
- Application Number
- CN202510008239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Lithium-ion batteries made from existing lithium iron phosphate materials have defects in performance such as cycle life, which limits their further promotion and use.
A modified conductive agent was used to prepare a lithium iron phosphate cathode slurry. The lithium iron phosphate cathode material was prepared by ball milling, sintering and mixing processes. A lithium/nickel coated nanoscale carbon black was formed on the surface of the lithium iron phosphate intermediate to improve conductivity and structural stability.
It improves the conductivity, structural stability and cycle performance of lithium iron phosphate cathode materials, extends battery life, and maintains good electronic conductivity under high-rate charge and discharge conditions.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium ion batteries, in particular to a lithium iron phosphate positive electrode slurry, a positive electrode sheet and a preparation method thereof, and a battery. BACKGROUND
[0002] Lithium ion batteries are a kind of green new energy that is currently attracting much attention, and have been widely used in electric vehicles and many electronic product fields, becoming a hot topic in the field of scientific research. Among them, phosphate positive electrode materials are a key component of lithium ion batteries, and lithium iron phosphate with an olivine structure has outstanding safety performance, low cost and strong cycle stability, and is considered as one of the most ideal choices among many phosphate materials.
[0003] A patent with application number 201810073892.6 discloses a composite lithium iron phosphate material, a preparation method thereof, a positive electrode sheet and a lithium ion battery. The composite lithium iron phosphate material in the patent is composed of the following components in mass percentage: lithium iron phosphate 75-85%, lithium nickel cobalt manganese oxide 10-25%, carbon nanotube 1-2%, and conductive carbon black 1-2%. The composite lithium iron phosphate material prepared by the patent is a high-energy-density composite lithium iron phosphate material, and the lithium iron phosphate, lithium nickel cobalt manganese oxide, carbon nanotube and conductive carbon black are mutually filled, reducing the porosity between the materials and improving the compaction density of the material.
[0004] The lithium iron phosphate material prepared in the above patent improves the performance of the battery, such as the relative discharge capacity and the relative discharge energy. However, the battery prepared from the lithium iron phosphate material has defects in terms of cycle performance, which limits the further use of the material. SUMMARY
[0005] In the manufacturing process of the battery, the positive electrode material needs to be first processed into a positive electrode slurry, and then further processed into a positive electrode sheet, and finally processed into a battery. The present application provides a preparation method of a lithium iron phosphate positive electrode slurry, which makes up for the defects of the finally prepared positive electrode sheet in terms of low compaction density and low conductivity, and the defects of the battery in terms of low gravimetric capacity and poor cycle performance.
[0006] The present application is achieved by the following technical solutions:
[0007] The application discloses a preparation method of a lithium iron phosphate positive electrode slurry, which comprises the following steps: S1. according to a first mass fraction, 15-78 parts of an iron source, 20-28 parts of a phosphorus source, 0.025-0.45 parts of a boron source, 4.6-15 parts of a lithium source, 1.1-6.5 parts of a carbon source and 80-200 parts of a dispersing agent are taken as raw materials, the raw materials are mixed and crushed to obtain a lithium iron phosphate intermediate; S2. the lithium iron phosphate intermediate is sintered and crushed to obtain a lithium iron phosphate positive electrode material; S3. according to a second mass fraction, 80-90 parts of the lithium iron phosphate positive electrode material, 5-10 parts of a binder and 5-10 parts of a conductive agent are taken and dissolved in a solvent to form a positive electrode slurry; wherein the conductive agent is lithium / nickel-coated nanoscale carbon black, which is prepared by reacting carbon black, lithium acrylate, allyl (cyclopentadienyl) nickel and amine-terminated polydimethylsiloxane.
[0008] As a further improvement of the application, in S1, the crushing step adopts ball milling processing, the rotating speed of the ball milling processing is 700-1000 r / min, the duration of the ball milling processing is 2-5 h, and after the ball milling processing is completed, the ball milling product is dried to obtain the lithium iron phosphate intermediate.
[0009] As a further improvement of the application, in S2, the lithium iron phosphate intermediate is sintered for three times in the sintering step, wherein the temperature of the first sintering is 600-750 DEG C, the duration is 2-5 h, the temperature of the second sintering is 850-950 DEG C, the duration is 10-15 h, and the temperature of the third sintering is 600-700 DEG C, the duration is 2-5 h.
[0010] As a further improvement of the application, in S2, the temperature is raised to 600-750 DEG C at a temperature raising rate of 2-5 DEG C / min during the first sintering.
[0011] As a further improvement of the application, in S2, the sintering is carried out in a nitrogen atmosphere or an inert gas atmosphere.
[0012] As a further improvement of the application, in S3, the preparation method of the conductive agent comprises the following steps: according to a third mass fraction, 5-10 parts of carbon black, 0.05-0.4 parts of lithium acrylate, 0.025-0.6 parts of allyl (cyclopentadienyl) nickel, 0.05-0.4 parts of amine-terminated polydimethylsiloxane and 0.1-0.5 parts of ethylenediamine are taken, and the above materials are mixed at a temperature of 90-100 DEG C for 10-20 min to obtain the lithium / nickel-coated nanoscale carbon black.
[0013] As a further improvement of the present application, the conductive agent is prepared by first adding 5-10 parts of carbon black and 0.05-0.4 parts of lithium acrylate in a mixing device; then adding 0.025-0.6 parts of allyl (cyclopentadienyl) nickel; finally introducing 0.05-0.4 parts of amine-terminated dimethyl polysiloxane and 0.1-0.5 parts of ethylenediamine. The mixing temperature is maintained at 90-100°C, and the mixing duration is 10-20 min, to obtain lithium / nickel-coated nanoscale carbon black.
[0014] As a further improvement of the present application, in S1, the iron source is at least one of ferric oxide, iron hydroxide, ferric acetate, ferrous oxalate, ferrocene, iron acetylacetone, and ferric citrate; the phosphorus source is at least one of phosphoric acid, lithium dihydrogen phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate; the boron source is at least one of boric acid, diboron trioxide, boron trifluoride, or boron nitride; the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, or lithium oxalate; the carbon source is at least one of carbon nanotube, carbon nanorod, carbon nanowire, glucose, starch, sucrose, or polyethylene glycol; the dispersant is at least one of ethylene glycol, n-butanol, methyl amyl alcohol, polyacrylamide, or fatty acid polyethylene glycol ester; in S3, the binder is at least one of carboxymethyl cellulose, polypropylene, polyethylene, polyethylene oxide, polyvinylidene fluoride, polyvinylidene difluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, and styrene-butadiene rubber.
[0015] In a second aspect, the present application provides a lithium iron phosphate positive electrode slurry prepared by any of the above-mentioned methods.
[0016] In a third aspect, the present application provides a method for preparing a positive electrode sheet, comprising the following steps: coating the above-mentioned lithium iron phosphate positive electrode slurry on the surface of a current collector to form a coated electrode sheet, and then sequentially performing preliminary drying, rolling, slicing, and secondary drying to obtain a positive electrode sheet; wherein the temperature of the preliminary drying is 100-110°C, and the duration is 30-45 min; the temperature of the secondary drying is 100-110°C, and the duration is 8-12 h.
[0017] In a fourth aspect, the present application provides a positive electrode sheet prepared by the above-mentioned method.
[0018] In a fifth aspect, the present application provides a battery comprising the above-mentioned lithium iron phosphate positive electrode slurry and / or the above-mentioned positive electrode sheet.
[0019] In the present application, the actual mass of each raw material involved in the first mass fraction, the actual mass of each raw material involved in the second mass fraction, and the actual mass of each raw material involved in the third mass fraction are not directly related to each other, and each of them is used to show the ratio relationship between the raw materials required for the lithium iron phosphate intermediate, the positive electrode slurry, and the conductive agent, so the actual mass of each raw material in the three mass fractions can be the same or different. For example, in the first mass fraction, 1 part of the raw material is 1g; in the second mass fraction and the third mass fraction, 1 part of the raw material can be 1g, or 2g, etc.
[0020] The present application has the beneficial effect that the modified conductive agent is introduced to alleviate the defects of the lithium iron phosphate positive electrode slurry in terms of conductivity, structural stability, and cycle performance.
[0021] In terms of conductive agent modification, the present application first uses amino-terminated polydimethylsiloxane to perform surface treatment on carbon black to obtain amino-modified carbon black; and then makes the amino-modified carbon black and lithium acrylate, allyl(cyclopentadienyl) nickel respectively perform amino-ene addition reaction to finally obtain lithium / nickel-coated nanoscale carbon black. The overall process of the conductive agent modification operation is relatively simple, and the required time is relatively short, which is conducive to the use of the technology in actual production and the popularization and use of the material.
[0022] The modified conductive agent has a plurality of beneficial effects and can effectively compensate for a plurality of defects of the lithium iron phosphate positive electrode material. First, the surface of the modified conductive agent is grafted with an organic silicon segment, and its surface properties change from hydrophilic to hydrophobic, which helps to improve the dispersibility of the conductive agent in the polymer matrix, reduce the agglomeration phenomenon, make the prepared positive electrode slurry easy to process, and meet the basic requirements of the positive electrode slurry.
[0023] Secondly, after the amino-modified carbon black and lithium acrylate and allyl(cyclopentadienyl) nickel perform amino-ene addition reaction, a uniform lithium and nickel layer will be formed on the surface of the carbon black. This metal or metal oxide coating can effectively reduce the contact resistance between carbon black particles, optimize the transmission path of electrons in the electrode material, and thus improve the conductivity of the positive electrode slurry.
[0024] At the same time, the surface of the modified conductive agent has better interfacial compatibility, can form a more stable combination with the lithium iron phosphate positive electrode material, thereby improving the transmission efficiency of electrons at the interface, and thus having a stronger interfacial interaction.
[0025] In addition, the volume change of the electrode material is caused by the embedding and de-embedding of lithium ions during the charging and discharging process, and the modified carbon black provided by the present application can absorb part of the stress after being added, so as to inhibit the volume expansion of the electrode material and maintain the stability of the electrode structure; and since the modified conductive agent has good conductivity and structural stability, it can reduce the performance decay of the electrode material during long-term cycling, thereby prolonging the service life of the battery.
[0026] Finally, as a conductive additive, the modified carbon black can ensure that the finally prepared battery still maintains good electronic conductivity under high-rate charging and discharging conditions, so that the battery can work stably under a large current, which is beneficial to widening the use scenarios of the battery. DETAILED DESCRIPTION
[0027] The present application will be further described in detail according to the embodiments.
[0028] In order to make the purpose, technical scheme and advantages of the present application more clear and explicit, the present application is further described in detail in combination with embodiments, and it should be understood that the specific embodiments described herein are only used to explain the present application, rather than all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the present application.
[0029] Embodiment 1
[0030] The present embodiment provides a preparation method of lithium iron phosphate positive electrode slurry and the lithium iron phosphate positive electrode slurry prepared thereby. In terms of materials used in the present embodiment, in the process of preparing the lithium iron phosphate intermediate, the iron source used is iron hydroxide; the phosphorus source is phosphoric acid; the boron source is boron nitride; the lithium source is lithium hydroxide; the carbon source is carbon nanotube; and the dispersing agent is ethylene glycol. In the process of preparing the positive electrode slurry, the solvent used is N-methyl pyrrolidone; and the binder is carboxymethyl cellulose.
[0031] In the present embodiment, the lithium iron phosphate positive electrode slurry is prepared by the following steps:
[0032] S1. 15 g of iron source, 20 g of phosphorus source, 0.025 g of boron source, 4.6 g of lithium source, 1.1 g of carbon source and 80 g of dispersing agent are weighed as raw materials, and the raw materials are directly mixed and then placed in a ball mill, and the rotation speed of the ball mill is set to 700 r / min; the duration is 2 h; after the ball milling work is completed, the ball milling product is dried to obtain a lithium iron phosphate intermediate.
[0033] S2. The lithium iron phosphate intermediate prepared in S1 is sintered three times under a nitrogen atmosphere. Firstly, the temperature is raised to 600 °C at a rate of 5 °C / min for the first sintering, and the duration is 2 h. Then, the temperature is raised to 850 °C for the second sintering, and the duration is 10 h. Finally, the temperature is lowered to 600 °C for the third sintering, and the duration is 2 h. After the sintering is completed, the material is cooled to 25 °C and crushed to obtain the lithium iron phosphate positive electrode material.
[0034] S3. 80 g of the lithium iron phosphate positive electrode material, 10 g of the binder, and 10 g of the conductive agent are weighed and added to the solvent and mixed uniformly to form a positive electrode slurry.
[0035] In this embodiment, the conductive agent used is lithium / nickel-coated nanoscale carbon black, which is prepared by the following method: the high-speed mixer is kept on, and during this period, 5 g of carbon black, 0.05 g of lithium acrylate are first added to the high-speed mixer in turn; then 0.025 g of allyl(cyclopentadienyl) nickel is added; finally, 0.05 g of amodimethicone and 0.1 g of ethylenediamine are introduced. After all the materials are added, the temperature in the high-speed mixer is kept at 90 °C, and the mixing is continued for 10 min to obtain the lithium / nickel-coated nanoscale carbon black, which is the required conductive agent.
[0036] Example 2:
[0037] The difference between this embodiment and Example 1 is in the materials used. In the preparation of the lithium iron phosphate intermediate, the iron source used is ferrous oxalate; the phosphorus source is lithium dihydrogen phosphate; the boron source is boric acid; the lithium source is lithium acetate; the carbon source is polyethylene glycol; and the dispersing agent is n-butanol. In the preparation of the positive electrode slurry, the solvent used is N-methylpyrrolidone; and the binder is polypropylene and styrene-butadiene rubber.
[0038] In this embodiment, the lithium iron phosphate positive electrode slurry is prepared by the following steps:
[0039] S1. 40 g of the iron source, 22 g of the phosphorus source, 0.15 g of the boron source, 8 g of the lithium source, 2.5 g of the carbon source, and 110 g of the dispersing agent are weighed as raw materials, and the raw materials are directly mixed and then placed in a ball mill. The rotation speed of the ball mill is set to 800 r / min, and the duration is 3 h. After the ball milling is completed, the ball milling product is dried to obtain the lithium iron phosphate intermediate.
[0040] S2. The lithium iron phosphate intermediate prepared in S1 is sintered three times under a nitrogen atmosphere. Firstly, the temperature is raised to 650 ℃ at a rate of 4 ℃ / min for the first sintering, and the duration is 3 h; then the temperature is raised to 875 ℃ for the second sintering, and the duration is 11.5 h; finally, the temperature is lowered to 625 ℃ for the third sintering, and the duration is 3 h. After the sintering is completed, the material is cooled to 25 ℃ and then crushed to obtain the lithium iron phosphate positive electrode material.
[0041] S3. 85 g of the lithium iron phosphate positive electrode material, 5 g of the binder and 10 g of the conductive agent are weighed and added to the solvent and mixed uniformly to form a positive electrode slurry.
[0042] In this embodiment, the conductive agent used is lithium / nickel-coated nanoscale carbon black, which is prepared by the following method: the high-speed mixer is kept on, and during this period, 6.5 g of carbon black, 1.5 g of lithium acrylate are first added to the high-speed mixer in sequence; then 2 g of allyl(cyclopentadienyl) nickel is added; finally, 0.15 g of amine-terminated polydimethylsiloxane and 0.2 g of ethylenediamine are introduced. After all the materials are added, the temperature in the high-speed mixer is kept at 95 ℃, and the mixing is continued for 13 min to obtain the lithium / nickel-coated nanoscale carbon black, which is the required conductive agent.
[0043] Example 3:
[0044] The difference between this embodiment and Example 1 is in the materials used. In the preparation of the lithium iron phosphate intermediate, the iron source used is a mixture of ferric oxide and ferrocene; the phosphorus source is a mixture of phosphoric acid and ammonium dihydrogen phosphate; the boron source is a mixture of boric acid and boron nitride; the lithium source is lithium carbonate; the carbon source is a mixture of carbon nanotubes and glucose; and the dispersing agent is methyl amyl alcohol. In the preparation of the positive electrode slurry, the solvent used is N-methyl pyrrolidone; and the binder is polyacrylonitrile.
[0045] In this embodiment, the lithium iron phosphate positive electrode slurry is prepared by the following steps:
[0046] S1. 50 g of the iron source, 24 g of the phosphorus source, 0.3 g of the boron source, 13 g of the lithium source, 5 g of the carbon source and 160 g of the dispersing agent are weighed as raw materials, which are directly mixed and then placed in a ball mill. The rotation speed of the ball mill is set to 900 r / min, and the duration is 4.5 h. After the ball milling is completed, the ball milling product is dried to obtain the lithium iron phosphate intermediate.
[0047] S2. The lithium iron phosphate intermediate prepared in S1 is sintered three times under a nitrogen atmosphere. Firstly, the temperature is raised to 700 °C at a rate of 3 °C / min for the first sintering, and the duration is 4 h. Then, the temperature is raised to 925 °C for the second sintering, and the duration is 13.5 h. Finally, the temperature is lowered to 675 °C for the third sintering, and the duration is 4 h. After the sintering is completed, the material is cooled to 25 °C and then crushed to obtain the lithium iron phosphate positive electrode material.
[0048] S3. 85 g of the lithium iron phosphate positive electrode material, 10 g of the binder, and 5 g of the conductive agent are weighed and added to the solvent and mixed uniformly to form a positive electrode slurry.
[0049] In this embodiment, the conductive agent used is lithium / nickel-coated nanoscale carbon black, which is prepared by the following method: the high-speed mixer is kept on, and during this period, 8 g of carbon black, 0.3 g of lithium acrylate are first added to the high-speed mixer in sequence; then 4 g of allyl(cyclopentadienyl) nickel is added; finally, 3 g of amine-terminated polydimethylsiloxane and 0.35 g of ethylenediamine are introduced. After all the materials are added, the temperature in the high-speed mixer is kept at 97 °C, and the mixing is continued for 18 min to obtain the lithium / nickel-coated nanoscale carbon black, which is the required conductive agent.
[0050] Example 4:
[0051] The difference between this embodiment and Example 1 is in the materials used. In the preparation of the lithium iron phosphate intermediate, the iron source used is acetylacetone iron; the phosphorus source is diammonium hydrogen phosphate; the boron source is di boron trioxide; the lithium source is lithium oxalate; the carbon source is sucrose; and the dispersing agent is methyl amyl alcohol. In the preparation of the positive electrode slurry, the solvent used is N-methyl pyrrolidone; and the binder is polyhexafluoropropylene.
[0052] In this embodiment, the lithium iron phosphate positive electrode slurry is prepared by the following steps:
[0053] S1. 78 g of the iron source, 28 g of the phosphorus source, 0.45 g of the boron source, 15 g of the lithium source, 6.5 g of the carbon source, and 200 g of the dispersing agent are weighed as raw materials, and the raw materials are directly mixed and then placed in a ball mill. The rotation speed of the ball mill is set to 1000 r / min, and the duration is 5 h. After the ball milling is completed, the ball milling product is dried to obtain the lithium iron phosphate intermediate.
[0054] S2. The lithium iron phosphate intermediate prepared in S1 is sintered three times under a nitrogen atmosphere, first, the temperature is raised to 750 ℃ at a rate of 2 ℃ / min for the first sintering, the duration is 5 h; then the temperature is raised to 950 ℃ for the second sintering, the duration is 15 h; finally, the temperature is lowered to 700 ℃ for the third sintering, the duration is 5 h. After sintering is completed, the material is cooled to 25 ℃ and crushed to obtain the lithium iron phosphate positive electrode material.
[0055] S3. 90 g of the lithium iron phosphate positive electrode material, 10 g of the binder and 10 g of the conductive agent are weighed into the solvent and mixed uniformly to form a positive electrode slurry.
[0056] In this embodiment, the conductive agent used is lithium / nickel-coated nanoscale carbon black, which is prepared by the following method: keep the high-speed mixer on, during which first 10 g of carbon black, 0.4 g of lithium acrylate are added into the high-speed mixer in turn; then 0.6 g of allyl(cyclopentadienyl) nickel is added; finally, 3 g of amine-terminated polydimethylsiloxane and 0.4 g of ethylenediamine are introduced. After all the materials are added, the temperature in the high-speed mixer is kept at 100 ℃, and the mixing is continued for 20 min to obtain the lithium / nickel-coated nanoscale carbon black, which is the required conductive agent.
[0057] Comparative Example 1:
[0058] The difference between this comparative example and Example 1 is that in this comparative example, the conductive agent used is carbon black. And since the carbon black is not modified, the preparation steps of the related conductive agent are not performed.
[0059] Comparative Example 2:
[0060] The difference between this comparative example and Example 1 is that in this comparative example, the conductive agent used is not added with lithium acrylate during preparation. The rest of the agents used and the processing steps remain consistent with the scheme in Example 1.
[0061] Comparative Example 3:
[0062] The difference between this comparative example and Example 1 is that in this comparative example, the conductive agent used is not added with allyl(cyclopentadienyl) nickel during preparation. The rest of the agents used and the processing steps remain consistent with the scheme in Example 1.
[0063] Performance detection:
[0064] The specific performance of the beneficial effects of the lithium iron phosphate positive electrode slurry is reflected in the performance of the positive electrode sheet and the battery prepared therefrom. Therefore, the performance detection in this embodiment is mainly carried out on the positive electrode sheet and the battery prepared from the lithium iron phosphate positive electrode slurry in Examples 1-4 and Comparative Examples 1-3.
[0065] Pre-experiment:
[0066] Before the detection, the positive electrode slurry of lithium iron phosphate in examples 1~4 and comparative examples 1~3 was firstly used to prepare the positive electrode sheet, and then the positive electrode sheet was combined with the remaining components of the battery to form the battery. In this embodiment, the current collector used in the preparation of the positive electrode sheet was aluminum foil.
[0067] For the lithium iron phosphate positive electrode slurry in examples 1 and comparative examples 1~3, the positive electrode slurry was coated on the surface of the aluminum foil, and then the coated aluminum foil was placed in an oven for preliminary drying at 100℃ for 30 min, and then the dried electrode sheet was sequentially rolled and sliced. Finally, it was placed in a vacuum oven for secondary drying at 100℃ for 8 h to obtain the positive electrode sheet.
[0068] For the lithium iron phosphate positive electrode slurry in example 2, the positive electrode slurry was coated on the surface of the aluminum foil, and then the coated aluminum foil was placed in an oven for preliminary drying at 103℃ for 40 min, and then the dried electrode sheet was sequentially rolled and sliced. Finally, it was placed in a vacuum oven for secondary drying at 103℃ for 9.5 h to obtain the positive electrode sheet.
[0069] For the lithium iron phosphate positive electrode slurry in example 3, the positive electrode slurry was coated on the surface of the aluminum foil, and then the coated aluminum foil was placed in an oven for preliminary drying at 108℃ for 43 min, and then the dried electrode sheet was sequentially rolled and sliced. Finally, it was placed in a vacuum oven for secondary drying at 108℃ for 11 h to obtain the positive electrode sheet.
[0070] For the lithium iron phosphate positive electrode slurry in example 4, the positive electrode slurry was coated on the surface of the aluminum foil, and then the coated aluminum foil was placed in an oven for preliminary drying at 110℃ for 45 min, and then the dried electrode sheet was sequentially rolled and sliced. Finally, it was placed in a vacuum oven for secondary drying at 110℃ for 12 h to obtain the positive electrode sheet.
[0071] After the corresponding positive electrode sheet was prepared, the corresponding positive electrode sheet was assembled with lithium sheet, separator and electrolyte in a button cell to form a button cell. In this embodiment, the separator used was polyethylene, the electrolyte used was LiPF6, and the solvent used was EC / DMC (a mixture of ethylene carbonate and dimethyl carbonate).
[0072] Main items of performance detection:
[0073] (1) Positive electrode sheet detection item
[0074] The positive electrode sheet is subjected to a compactness density test, and the lithium iron phosphate positive electrode material on the surface of the positive electrode sheet is subjected to a conductivity test. The compactness density test step is performed by referring to the method described in "Lithium ion battery positive electrode material Powder compactness density determination" (GB / T44330-2024); the conductivity test is detected by using a four-probe tester.
[0075] (2) Battery detection item
[0076] The initial specific capacity and capacity retention rate of the battery are detected.
[0077] The detection steps include: fully charging the battery in a normal temperature (25℃) environment, then fully standing in the normal temperature environment, discharging to the cut-off voltage (2.5V) at 1C rate, recording the released capacity. Then, in the normal temperature, constant current 1C charging, cut-off current 0.05C, static 10min, 0.7C discharging, sequentially circulating 1000 times, and calculating the capacity retention rate of 1000 times of circulation.
[0078] The performance detection results of the positive electrode sheet and the battery are shown in Table 1:
[0079] Table 1 Performance detection result statistics
[0080] Compacted density (g / m 3 ) conductivity (S / cm) initial specific capacity (mAh / g) capacity retention rate (%) after 1000 cycles Example 1 2.6 0.058 155.8 92.6 Example 2 2.8 0.062 164.7 93.1 Example 3 2.9 0.066 170.3 94.3 Example 4 3.1 0.072 180.4 95.4 Comparative Example 1 1.2 0.028 104.5 80.2 Comparative Example 2 1.8 0.037 121.2 85.1 Comparative Example 3 1.9 0.041 127.5 87.4
[0081] Among them, the positive electrode slurries in Examples 1-5 all use modified carbon black as the conductive agent, while the positive electrode slurry in Comparative Example 1 uses unmodified carbon black, and the positive electrode slurries in Comparative Examples 2-3 use carbon black that is not modified to the required standard.
[0082] From the detection results in Table 1, it can be seen that the compactness densities of the positive electrode sheets prepared from the positive electrode slurries in Examples 1-4 all reach 2.0-3.5 g / m 3 , which meets the compactness density requirement of the positive electrode sheet when lithium iron phosphate is used as the positive electrode material. If the compactness density is too high, it may cause the porosity to decrease, hinder the diffusion of lithium ions, and affect the charge and discharge efficiency of the battery; if the compactness density is too low, it may cause the active material utilization rate to be low. The positive electrode sheets prepared from the positive electrode slurries in Examples 1-4 have appropriate compactness densities, while the positive electrode sheets prepared from the positive electrode slurries in Comparative Examples 1-3 have relatively low compactness densities, which can also be confirmed by the remaining performance detection results. This shows that the amounts of the binder and the conductive agent provided in Examples 1-4 are appropriate, which can adapt to the modified conductive agent, so that it can play the corresponding beneficial effects.
[0083] And through the remaining test results in Table 1, it can be seen that the conductivity of the positive electrode plate prepared from the positive electrode slurry in Examples 1-4 is significantly stronger than that of the positive electrode plate prepared from the positive electrode slurry in Comparative Examples 1-3; the initial specific capacity and the capacity retention rate after 1000 cycles of the battery finally prepared from the positive electrode slurry in Examples 1-4 are also better than those of the battery finally prepared from the positive electrode slurry in Comparative Examples 1-3.
[0084] Among them, the stronger conductivity of the positive electrode plate prepared from the positive electrode slurry in Examples 1-4 confirms the inventor's speculation that the modified conductive agent can reduce the contact resistance between carbon black particles through the lithium layer and the nickel layer, optimize the transmission path of electrons inside the electrode material, and thus improve the conductivity of the prepared positive electrode plate.
[0085] And the capacity retention rate after 1000 cycles of the battery prepared from the positive electrode slurry in Examples 1-4 is still relatively high, and is significantly higher than the capacity retention rate of the battery prepared from the positive electrode slurry in Comparative Examples 1-3, which confirms that the modified conductive agent can absorb the stress generated during lithium ion insertion and extraction, maintain the stability of the electrode structure, reduce the performance decay of the electrode material during long-term cycling, and thus prolong the service life of the battery. At the same time, since the capacity retention rate after 1000 cycles of the battery prepared from the positive electrode slurry in Examples 1-4 is measured under the experimental conditions of 1C current, it also indicates that the battery can still maintain long-term stable operation under high-rate charging and discharging conditions.
[0086] Overall, the comprehensive performance of the positive electrode plate and the battery prepared from the positive electrode slurry in Examples 1-4 is better than that of the positive electrode plate and the battery prepared from the positive electrode slurry in Comparative Examples 1-3, which confirms that the modified conductive agent has better interfacial compatibility and can form a more stable combination with the lithium iron phosphate positive electrode material, thereby improving the performance of the positive electrode plate and the battery by improving the transmission efficiency of electrons at the interface.
[0087] The mutual confirmation of various data indicates that the modified conductive agent selected in Examples 1-4 of the present application has excellent performance, and the amounts of the provided binders, conductive agents and other raw materials are appropriate. The prepared positive electrode plate and battery meet the use requirements, can improve some defects of the lithium iron phosphate positive electrode material during use, and ultimately improve the related performance of the prepared battery.
[0088] Finally, it should be noted that: the above implementation cases are only used to illustrate the technical solutions of the present application, but not to limit them; although the present application has been described in detail with reference to the foregoing implementation cases, those skilled in the art should understand that: they can still modify the technical solutions recorded in the foregoing implementation cases, or make equivalent substitutions for part of the technical features; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation cases of the present application.
Claims
1. A method of preparing a lithium iron phosphate cathode slurry, characterized by, Comprising the following steps: S1. According to the first mass fraction, 15~78 parts of iron source, 20~28 parts of phosphorus source, 0.025~0.45 parts of boron source, 4.6~15 parts of lithium source, 1.1~6.5 parts of carbon source and 80~200 parts of dispersing agent are weighed as raw materials, and the raw materials are mixed and crushed to obtain a lithium iron phosphate intermediate; S2. The lithium iron phosphate intermediate is sintered and crushed to obtain a lithium iron phosphate positive electrode material; S3. According to the second mass fraction, 80~90 parts of lithium iron phosphate positive electrode material, 5~10 parts of binder and 5~10 parts of conductive agent are weighed and dissolved in a solvent to form a positive electrode slurry; Wherein, the conductive agent is lithium / nickel coated nanoscale carbon black, which is prepared by reacting carbon black, lithium acrylate, allyl(cyclopentadienyl) nickel and amine-terminated polydimethylsiloxane. According to the third mass fraction, 5~10 parts of carbon black, 0.05~0.4 parts of lithium acrylate, 0.025~0.6 parts of allyl(cyclopentadienyl) nickel, 0.05~0.4 parts of amine-terminated polydimethylsiloxane and 0.1~0.5 parts of ethylenediamine are weighed. The above materials are mixed at a temperature of 90~100℃ for 10~20 min to obtain the lithium / nickel coated nanoscale carbon black.
2. The method of claim 1, wherein the lithium iron phosphate cathode slurry is prepared by the steps of: In S1, the crushing step adopts ball milling processing, the rotation speed of the ball milling processing is 700~1000 r / min; the duration of the ball milling processing is 2~5 h; after the ball milling processing is completed, the ball milling product is dried to obtain the lithium iron phosphate intermediate. 3. The method for preparing a lithium iron phosphate cathode slurry according to claim 1, characterized in that, In S2, the lithium iron phosphate intermediate is sintered three times in the sintering step, wherein the temperature of the first sintering is 600~750℃, the duration is 2~5 h, the temperature of the second sintering is 850~950℃, the duration is 10~15 h, and the temperature of the third sintering is 600~700℃, the duration is 2~5 h.
4. The method for preparing a lithium iron phosphate cathode slurry according to claim 1, characterized in that, In S2, the sintering is carried out in a nitrogen atmosphere or an inert gas atmosphere.
5. The method for preparing lithium iron phosphate positive electrode slurry according to any one of claims 1 to 4, characterized in that, In S1, the iron source uses at least one of ferric oxide, iron hydroxide, iron acetate, ferrous oxalate, ferrocene, acetylacetone iron, and ferric citrate; the phosphorus source uses at least one of phosphoric acid, lithium dihydrogen phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate; the boron source uses at least one of boric acid, boron trioxide, boron trifluoride, and boron nitride; the lithium source uses at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, and lithium oxalate; the carbon source uses at least one of carbon nanotubes, carbon nanorods, carbon nanowires, glucose, starch, sucrose, and polyethylene glycol; the dispersing agent uses at least one of ethylene glycol, n-butanol, methyl pentanol, polyacrylamide, and fatty acid polyethylene glycol ester; in S3, the binder uses at least one of carboxymethyl cellulose, polypropylene, polyethylene, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, and butadiene styrene rubber.
6. A lithium iron phosphate cathode slurry characterized by, The lithium iron phosphate positive electrode slurry is prepared by the method in any one of claims 1-5.
7. A method of making a positive electrode sheet, characterized by, The method comprises the following steps: The lithium iron phosphate positive electrode slurry in claim 6 is coated on the surface of the current collector to form a coated electrode sheet, and the coated electrode sheet is sequentially subjected to preliminary drying, rolling, slicing and secondary drying to obtain a positive electrode sheet. The temperature of the preliminary drying is 100-110 DEG C, and the duration is 30-45 min; the temperature of the secondary drying is 100-110 DEG C, and the duration is 8-12 h.
8. A positive electrode sheet characterized by comprising: The positive electrode sheet is prepared by the method in claim 7.
9. A battery, characterized by The method comprises the following steps: using the lithium iron phosphate positive electrode slurry in claim 6 or the positive electrode sheet in claim 8.
Citation Information
Patent Citations
Compound lithium iron phosphate material and preparing method thereof, positive electrode piece and lithium ion battery
CN108288699A
Lithium ion battery taking graphene as cathode paste conductive agent
CN106558729A
Production process of battery positive electrode slurry dispersing agent
CN118712386A